Rethinking Teacher Training According to 21st Century Competences - Voinea, Mihaela (European Journal of Multidisciplinary Studies, 2019)
One of the demands of our educational system is the orientantion towards sustenability. To prepare people for future we need teachers who are able to develop the 21stcentury competences – the six macro-level competences are considered universally relevant: life-long learning, multi-literatenes, trans-disciplinarity, self-agency, interacting with others and interacting in and with the world. (Marope, 2018). This article focuses on researching the way in which pedagogical practices are changed and on studying the factors which are involved in educational changes. A longitudinaly study on ten years (2008-2018) was set up. Our purpose was to look for and describe how the educational practice has changed. The changes in educational practices are produced when they are sustained by educational politics and environmental factors as well as the teacher`s abilities and traits: reflections, novelty, openness, learning, critical thinking. The gap between present educational practice and future demands can be reduced if system teacher training is rethought according to 21stcentury competences. Transformative learning in teacher training is an adequate way of developing teacher`s competences.